Intra-Population Variation of Secondary Metabolites in Cistus ladanifer L. - Cristina Valares Masa; Juan Carlos Alías Gallego; Natividad Chaves Lobón; Teresa Sosa Díaz (Molecules, 2016)
In previous studies, secondary metabolites in the leaf exudate of Cistus ladanifer, specifically aglycone flavonoids and diterpenes, were demonstrated to play an ecophysiological role. They protect against ultraviolet radiation, have antiherbivore activity, and are allelopathic agents. Their synthesis in the plant was also found to vary quantitatively and qualitatively in response to various environmental factors. In view of these findings, the present work was designed to clarify whether within a single population there are differences among individuals subject to the same environmental conditions. To this end, we analyzed the leaves of 100 individuals of C. ladanifer. The results showed the existence of intrapopulational variation, since, although all the individuals had the same composition of secondary chemistry, the amounts were different. The individuals of a given population of C. ladanifer differ from each other even when growing under similar conditions. According to the ammount of flavonoids and diterpenes observed in each individual, it was possible to distinguish four different groups of individuals. Most individuals, evenly distributed within the population, had low concentrations of the studied compounds, whilst other individuals synthesized greater amounts and were randomly distributed among the former. Given the functions of flavonoids and diterpenes in this species, the quantified intra-population variation may involve greater plasticity for the species in the face of environmental changes.